2007
DOI: 10.1590/s1676-06032007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mangrove extension at the Pacoti River estuary, CE, NE Brazil due to regional environmental changes between 1958 and 2004

Abstract: Regional land use changes at the Pacoti River basin, Ceará State, NE Brazil resulted in doubling the mangrove area from 1958 (0.71 km 2 ) to 2004 (1.44 km 2 ). Most of the increase was due to the replacing of salt marsh vegetation inland, but also along newly formed islands and enlarged river banks. Drastic reduction in freshwater supply and sediment accumulation due to river damming were probably the major drivers of the increased mangrove cover. However, changes due to global climate changes can not be ruled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 7 publications
3
30
0
1
Order By: Relevance
“…This expansion rate was higher in swamps that have undergone hydrological changes due to engineering works but also occurred in other locations, without direct anthropogenic influence. Engineering works, such as dams, wave breakers and other coastal interventions are capable of maximizing the effects of climate change on mangroves (Lacerda et al 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This expansion rate was higher in swamps that have undergone hydrological changes due to engineering works but also occurred in other locations, without direct anthropogenic influence. Engineering works, such as dams, wave breakers and other coastal interventions are capable of maximizing the effects of climate change on mangroves (Lacerda et al 2007.…”
mentioning
confidence: 99%
“…A study conducted by Lacerda et al (2007) on the mangrove expansion at the Pacotí River estuary, in the metropolitan region of Fortaleza, state of Ceará, showed that, in addition to colonizing old salt pits, mangroves also grew on recently enlarged estuarine islands and beaches. According to the authors, between 1958 and 1999, six new islands emerged in the estuary.…”
mentioning
confidence: 99%
“…CHAALALI et al, 2013) of PAC and PIR in the dry season led to changes in the species composition, with an emergence of marine species and a decrease in phytoplankton biomass. LACERDA et al (2007) ) mostly due to alterations in freshwater supply and sediment accumulation in consequence of river damming. Changes due to climate changes were also not ruled out by these authors.…”
Section: Discussionmentioning
confidence: 99%
“…, Lacerda et al. ;), adding to the probable influence of estuarine stress on H. emarginata in this area. The main impact seems to result from river damming, which has led to the formation of islands that are being covered by mangrove forest, partly occupying the habitat of other estuarine species (Lacerda et al.…”
Section: Discussionmentioning
confidence: 99%